Assertive outreach teams in London: models of operation. Pan-London Assertive Outreach Study, part 1. - Wright, C; Burns, T; James, P; Billings, J; Johnson, S; Muijen, M; Priebe, S; Ryrie, I; Watts, J; White, I (2003)
BACKGROUND: Assertive outreach teams have been introduced in the UK, based on the assertive community treatment (ACT) model. It is unclear how models of community care translate from one culture to another or the degree of adaptation that may result. AIMS: To characterise London assertive outreach teams and determine whether there are distinct groups within them. METHOD: Semi-structured interviews with team managers plus one month's prospective process of care data collection were used to test for 'model fidelity' to ACT and, by cluster analysis, to identify groupings. RESULTS: Fidelity varied widely, with four teams (out of 24 studied) rated 'high fidelity' and three teams rated 'low fidelity' by US standards and 17 rated 'ACT-like'. Three clusters were identified, with voluntary sector teams being the most distinct group. CONCLUSIONS: There is wide variation in the practice of assertive outreach in London. The role of the voluntary sector requires increased attention. Heterogeneity in practice is a clinical challenge but a research opportunity in distinguishing effective from redundant components of the approach.